Sex differences in outcomes of total hip arthroplasty for the treatment of ankylosing spondylitis - Zhang, Liang; Li, Hong-Chao; Man, Si-Liang; Bian, Tao; Dou, Yong; Liu, Wei; Zhou, Yi-Xin (Chinese medical journal, 2021)
The objectives of this study were to determine: (1) whether there were significant differences between female and male AS patients on baseline patient demographics, clinical, and laboratory characteristics and (2) whether gender affected outcomes following THA on AS patients significantly. The study was approved by the Institutional Research Ethics Committee of Beijing Jishuitan Hospital (No. 202004-83). Descriptive analysis of categorical variables was presented in the form of percentages and frequencies, and descriptive analysis of continuous variables was shown as mean and standard deviation or median and quartile (25%–75%) if the data were skewed. On the contrary, it was generally recognized that female AS patients showed a higher disease burden concerning disease activity and pain scores, including BASDAI, BASFI, and quality of life.